Variations on primary metabolites of the carrageenan-producing red algae Sarcopeltis skottsbergii from Chile and Sarcopeltis antarctica from Antarctic Peninsula - Pasqualetti, Cesar B.; Carvalho, Maria Angela M.; Mansilla, Andres; Avila, Marcela; Colepicolo, Pio; Yokoya, Nair S. (Frontiers in Marine Science, 2023)
Several studies reported that gametophytes and tetrasporophytes of Gigartinaceae produce different carrageenan types, as observed in Sarcopeltis species although they have isomorphic haploid and diploid phases. Cystocarpic and sterile plants of S. skottsbergii produced kappa-carrageenans, while tetrasporophytes produced lambda-carrageenans, and yields were higher in cystocarpic and sterile specimens than in tetrasporophytes. However, comparison on the other primary metabolites among different life history phases still needed to be investigated. Then, we tested the hypothesis if the variation on primary metabolites (pigments, proteins and carbohydrates) are related to the life history phases of S. antarctica and S. skottsbergii, and/or are influenced by abiotic factors. Primary metabolites of Sarcopeltis antarctica varied according to the life-history phases, as evidenced by PCA analysis. Non-fertile specimens presented higher phycobiliprotein concentrations, tetrasporophytes presented higher chlorophyll a concentrations, and cystocarpic specimens presented higher concentrations of proteins, polysaccharides and floridean starch. However, primary metabolites of S. skottsbergii varied in response to heterogenous abiotic environmental conditions of collecting sites of the southern Chile, and PCA analysis showed two groups; one was related by the higher nitrate and phosphate concentrations, and the other was related to the higher temperatures and lower salinities. Concentrations of floridean starch, low molecular weight carbohydrates, and polysaccharides are higher in S. antarctica than in S. skottsbergii, which could be related to the Antarctic environmental conditions, and the carbohydrate metabolism is important to survive in extreme environments.